E-Learning dengan Menggunakan COI Framework - Kosasih, Lydiawati; Iqbal, Muhammad (Bina Nusantara University, 2013)
This study discusses some considerations in education to achieve a good quality of learning by utilizing technological advances such as E-Learning. This study uses a model of Community of Inquiry (COI) as a comparative study to improve the quality of E-Learning program. Implementation of COI model in discussionforum on BiNusMaya through E-Learning is able to improve the quality of a discussion as improvement of knowledge management. This study aims to provide a proposal to the Department of Information Systems Bina Nusantara University in enhancing the effectiveness of the use of discussion forums on BiNusMaya (ELearning). By presenting the survey results related to the Binusmaya current condition,s such constraints and development expectations of both the lecturers and students for Binusmaya can be described. In addition, the application of CoI model is presented in a learning process especially when meeting outside of class (without face-to-face). The results of this study is expected to be the basis for developing a COI model design and implementation plan in Management Information Systems course, that may improve the quality of the use of discussion forums as part of the knowledge management process in future study.